Dhikr Ism Al-Dhat: Tuntutan Amalannya Dalam Al-Quran - Syed Omar, Syed Hadzrullathfi; Musa, Razali; Engku Wok Zin, Engku Ibrahim; Othman, Mohd Shahril (2009)
Dhikr ism al-dhat, which is repeatedly reciting the essence divine "Allah" verbally or in heart, is one of the methods in the remembrance of God and has been accepted by many Islamic scholars. Hence, this article tries to reveal the concept, through an analysis of various Qur'anic verses whether it is derived from many Quranic verses which have emphasized the importance of remembering God. As weII, the article also attempts to highlight the invocation's contribution to achieving the station (maqam) of ihsan as an ultimate aim which is mentioned in sunnah'